Description of Covid-19 Prevention In Community - Suradi Efendi; Esse Puji Pawenrusi; Nour Sriyanah; Rahmawati Rahmawati; Hilmiah Hilmiah (Jurnal Keperawatan, 2022)
Coronavirus Disease 2019 (COVID-19) is a new type of disease that has not been previously discovered in humans. According to the World Held Organization (WHO), so far the prevention methods that can be done by the community against Covid-19 so as not to be infected are washing hands with soap, physical distancing, and wearing masks. The purpose of this study was to describe the prevention of Covid-19 in the community in Buakg Village, Bungaya District, Gowa Regency. This type of research is descriptive. The population in this study is the productive age group of 1,024 people with a sample of 97 people taken by accidental sampling technique. The instrument in the study used a google form questionnaire. The results of this study indicate that of the 10 questions on hand washing with soap, 97 respondents answered yes to the most (100.0%), the most respondents answered no to 76 respondents (78.4%). Of the 5 questions about keeping a distance, the respondents who answered yes the most were 96 respondents (99.0%), the respondents who answered the most were no as many as 45 respondents (46.4%). Of the 10 questions about wearing masks, the respondents who answered yes the most were 96 respondents (99.0%), the respondents who answered no the most were 94 respondents (96.9%). The conclusion of this research is that in the prevention of Covid-19 in the community, it is not yet fully implemented and complied with the Health protocol. It is recommended to the community to maintain and even improve, carry out Health protocols.